Redesign Of Constitutional Mechanism For The Dissolution Of Political Parties: Comparative Study Of Indonesia and Germany (Redesain Mekanisme Konstitusional Pembubaran Partai Politik: Kajian Perbandingan Indonesia dan Jerman) - Oly Viana Agustine (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2018)
Dissolution of political parties is an authority that is monopolized by the Indonesian Constitutional Court and the Federal Constitutional Court of Germany. In contrast to the dissolution of associations, political parties have an important role in determining government policies that require specifically in the constitution. The Federal Constitutional Court of Germany has until now received nine requests for the dissolution of a political party with five decisions, namely two dissolutions granted and three dismissal of a political party has been rejected. While the Indonesian Constitutional Court since its establishment has never examined the dissolution of political parties. Thus it becomes an important and interesting thing to uncover the problem of dissolution of political parties in Germany in order to find the right policy in Indonesia. Normative juridical research methods are used in this study with case studies and comparison approaches. The conclusion obtained is that the dissolution of political parties denied the right of association and assembly which is endorsed by the constitution. The German Constitutional Court has disbanded political parties proportionally by examining and deciding on the dissolution of political parties not only in text but also in the context which meet the criteria of ”clear and present danger” to the sovereignty of the German Federal Government and the free democratic basic order. Therefore, it is necessary to redesign the disruption of the dissolution of political parties in Indonesia with empirical sociological and psychological studies in order to meet the ”clear and present danger” criteria.AbstrakPembubaran partai politik merupakan kewenangan yang dimonopoli, baik oleh Mahkamah Konstitusi Indonesia maupun Mahkamah Konstitusi Federal Jerman. Pembubaran partai politik berbeda dengan pembubaran organisasi lain, dikarenakan partai politik memiliki peran yang penting dalam penentuan kebijakan pemerintah yang pembatasannya perlu diatur khusus dalam konstitusi. Mahkamah Konstitusi Federal Jerman hingga saat ini telah menerima sembilan kali permohonan pembubaran partai politik dengan lima putusan yakni dua permohonan pembubaran dikabulkan dan tiga permohonan pembubaran partai politik ditolak. Sedangkan Mahkamah Konstitusi Indonesia sejak berdiri belum pernah memeriksa pembubaran partai politik. Dengan demikian, menjadi hal penting dan menarik untuk menganalisa mekanisme pembubaran partai politik di Jerman agar dapat ditemukan mekanisme yang tepat dalam pembubaran partai politik di Indonesia. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan studi kasus dan perbandingan. Kesimpulan yang didapat dalam penelitian ini adalah pembubaran partai politik merupakan pembatasan hak berserikat dan berkumpul yang disahkan oleh konstitusi. Mahkamah Konstitusi Jerman telah melaksanakan pembubaran partai politik secara proporsional dengan memeriksa dan memutus pembubaran partai politik tidak hanya secara teks tetapi juga konteksnya yang memenuhi kriteria “clear and present danger” terhadap kedaulatan Pemerintah Federal Jerman dan tatanan demokrasi yang bebas. Oleh karena itu, perlu dilakukan desain ulang mekanisme pembubaran partai politik di Indonesia dengan kajian sosiologis dan psikologis secara empiris agar memenuhi kriteria “clear and present danger”.